(untitled) (Research, Society and Development, 2025)
Brazil, marked by miscegenation and the legacy of slavery, presents deep social inequalities that still affect Black and quilombola communities, reflected in limited access to healthcare services and a high prevalence of diseases. This study aimed to analyze the quality of life of residents in the Pastinho quilombola community, located in Tanhaçu-BA and officially recognized in 2013 by the Fundação Cultural Palmares. The research, descriptive and quantitative in nature, was conducted between January and March 2025 through structured questionnaires addressing sociodemographic variables, housing conditions, health, nutrition, and work, applied to 69 of the 110 families in the community. Data were organized in spreadsheets and analyzed using the JASP software, with descriptive statistics and Pearson’s chi-square test, adopting a significance level of 5% (p<0.05). Results showed a predominance of female respondents (95.65%) with a mean age of 45.49 years. Educational fragility was observed, with 50.72% having incomplete primary education and 18.84% being illiterate. Most residents work in informal occupations, especially in agriculture, and the community faces the absence of basic sanitation, safe drinking water, and waste collection. In terms of health, 57.97% reported at least one chronic disease, such as hypertension or diabetes, and about 20% reported multiple comorbidities; there were no frequent reports of monogenic diseases, such as sickle cell anemia. It is concluded that the Pastinho community presents significant social and health vulnerabilities, highlighting the need for specific public policies to promote health equity.